Effect of scandium atoms substitution on the two-slab structure of scandate BaGd2Sc2O7 - Titov, Y.A.; Belyavina, N.M.; Slobodyanik, M.S.; Nakonechna, O.I.; Strutynska, N.Yu.; Chumak , V.V. (Physics and Chemistry of Solid State, 2023)
Tetragonal crystal structure (space group P42/mnm (No 136)) of the isovalently substituted BaGd2Sc2-xInxO7 phase with x = 0.5 was determined by X-ray powder diffraction methods. The crystal structure of BaGd2Sc1.5In0.5O7 consists of two-dimensional perovskite-like blocks with a thickness of two slabs of (Sc,In)O6 octahedra connected by vertices. A slab of GdO9 polyhedra is located between the blocks. There are no direct (Sc,In) – O – (Sc,In) connections between the octahedra of adjacent blocks. They are "stitched" to each other with the help of – O – Gd – O – bonds. Ba atoms are arranged only in the cubooctahedral voids of the perovskite-like block and their coordination number is 12. Analysis of the crystal chemical characteristics of BaGd2Sc2O7 and BaGd2Sc1.5In0.5O7 showed that upon the isovalent substitution of Sc atoms by large In atoms in slab perovskite-like structure leads to increase of the deformation degree of (Sc,In)O6 octahedra, GdO9 interblock polyhedra, increase in average (Sc,In) – O bond length and a decrease the degree deformation of BaO12 cuboctahedrons. Such changes lead to the destabilization of the slab perovskite-like structure and determine the limitation of the area of BaGd2Sc2-xInxO7 solid solutions and the absence of BaGd2In2O7 compound.